Alien species and evolution : the evolutionary ecology of exotic plants, animals, microbes, and interacting native species - Cox, George W., 1935- (Island Press, 2004)
Annotation Reviews and synthesises emerging information on the evolutionary changes that occur in plants, animals, and microbial organisms when they colonise new geographical areas, and on the evolutionary responses of the native species with which alien species interact.